Influence of phase change material properties on heat storage and discharge characteristics of latent heat thermal battery for solar thermal applications - Dheep G.R.; Verma Y.K.; Gupta S.K.; Jit S. (My University, 2025)
The present work focuses on analyzing the thermal reliability and corrosion properties of shell and tube heat exchanger system. In this work, Polyethylene Glycol 4000 is used as phase change material (PCM). PEG 4000 is subjected to accelerated thermal cycling tests to study the thermal reliability and corrosion properties of the PCM. The thermal reliability study of PEG 4000 shows that the change in melting temperature and latent heat of fusion after 1000 thermal cycles is − 1.66% and − 1.92%. Thermal performances such as charging and discharging properties of latent heat storage system incorporated with PEG 4000 PCM are also analyzed in the present work for different mass flow rates of a heat transfer fluid (HTF). Further, a shell and tube heat exchanger based latent heat storage system is developed to investigate the heat storage characteristics of PEG 4000. The temperature of HTF is maintained at 80 °C and 25 °C during charging and discharging of thermal energy. The thermal charging duration for different mass flow rates of HTF at 3, 4, and 5 kg min−1 were 45, 65, and 85 min, respectively. Similarly, during discharge the mass flow rate of HTF is maintained at 2 and 3 kg min−1. The thermal discharging duration for the corresponding mass flow rate is 20 and 15 min, respectively. The analysis reveals that the PEG 4000 is stable in terms of chemical, thermal, less corrosive and has good heat transfer characteristics. © Akadémiai Kiadó Zrt 2025.